Agroecology and Corporal Culture: an ethical-political proposal for Physical Education in Rural Education - Leonardo Lemos Silveira; Giovanni Frizzo; Carla Rosane Mota; Bruno Nicanor da Silva; Mayara Galvão Gonçalves (Universidade Federal do Norte do Tocantins, 2023)
The objective of this text is to systematize an ethical-political proposal for Physical Education in Rural Education, as a subsidy for the organization of pedagogical work based on the experience we developed with the Technical Course in Agroecology, in an integrated way, at the Escola Família Agrícola da Região Sul in Rio Grande do Sul. This systematization is intended to accumulate elements to contribute to the pedagogical work of Physical Education based on the principles of Rural Education, Agroecology, Pedagogy of Alternation and Corporal Culture as a reference basis for the teaching and learning processes.